2020
DOI: 10.1093/jn/nxaa128
|View full text |Cite
|
Sign up to set email alerts
|

A-Type Cinnamon Procyanidin Oligomers Protect Against 1-Methyl-4-Phenyl-1,2,3,6-Tetrahydropyridine-Induced Neurotoxicity in Mice Through Inhibiting the P38 Mitogen-Activated Protein Kinase/P53/BCL-2 Associated X Protein Signaling Pathway

Abstract: ABSTRACT Background Parkinson's disease (PD) is a common neurodegenerative disorder. Cinnamon procyanidin oligomers (CPOs) are flavonoids with many claimed health benefits. Objective This study aimed to elucidate the neuroprotection of A-type CPOs (CPO-A) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…Apart from cinnamaldehyde, cinnamon also contains various polyphenols, exerting significant antioxidant and anti‐inflammatory properties. [ 34 ] Among them, the A‐type cinnamon procyanidin oligomers (CPO‐A) represent the main biologically active polyphenols of cinnamon. [ 34 ] In vitro evidence has shown that treatment of MPP + ‐intoxicated SH‐SY5Y cells with 12.5 μM of CPO‐A may inhibit ROS accumulation and MPP + ‐induced neurotoxicity, via its implication in the P38 MAPK/P53/BCL‐2 associated X protein (BAX) signaling pathway.…”
Section: Effects Of Cinnamon and Its Metabolites In Pd: In Vitro Evidmentioning
confidence: 99%
See 4 more Smart Citations
“…Apart from cinnamaldehyde, cinnamon also contains various polyphenols, exerting significant antioxidant and anti‐inflammatory properties. [ 34 ] Among them, the A‐type cinnamon procyanidin oligomers (CPO‐A) represent the main biologically active polyphenols of cinnamon. [ 34 ] In vitro evidence has shown that treatment of MPP + ‐intoxicated SH‐SY5Y cells with 12.5 μM of CPO‐A may inhibit ROS accumulation and MPP + ‐induced neurotoxicity, via its implication in the P38 MAPK/P53/BCL‐2 associated X protein (BAX) signaling pathway.…”
Section: Effects Of Cinnamon and Its Metabolites In Pd: In Vitro Evidmentioning
confidence: 99%
“…[ 34 ] Among them, the A‐type cinnamon procyanidin oligomers (CPO‐A) represent the main biologically active polyphenols of cinnamon. [ 34 ] In vitro evidence has shown that treatment of MPP + ‐intoxicated SH‐SY5Y cells with 12.5 μM of CPO‐A may inhibit ROS accumulation and MPP + ‐induced neurotoxicity, via its implication in the P38 MAPK/P53/BCL‐2 associated X protein (BAX) signaling pathway. [ 34 ] Stress signals can lead to P38 phosphorylation and subsequent activation.…”
Section: Effects Of Cinnamon and Its Metabolites In Pd: In Vitro Evidmentioning
confidence: 99%
See 3 more Smart Citations